Changing course ideas, politics, and the Soviet withdrawal from Afghanistan - Mendelson, Sarah Elizabeth (Princeton Univ. Press, 1998)
In Changing Course, Sarah Mendelson demonstrates that interpretations which stress the impact of the international system, and particularly of U.S. foreign policy, or which focus on the role of ideas or politics alone, fail to explain the contingent process of change. Mendelson tells a story of internal battles where "misfit" ideas - ones that severely challenged the status quo - were turned into policies. She draws on firsthand interviews with those who ran Soviet foreign policy and the war in Afghanistan, and on recently declassified material from Soviet archives, to show that both ideas and political strategies were needed to make reform happen.
Keywords: Geschichte 1979-1991; Geschichte 1985-1991; Außenpolitik; Geschichte; Politik; Afghanistan-Konflikt -- 1979-1989; Neues Denken -- Sowjetunion; Afghānistān - Histoire - 1979-1989 (Intervention soviétique); URSS - Politique et gouvernement - 1985-1991; URSS - Relations extérieures - 1985-1991; URSS - Relations extérieures - Afghanistan; Sowjetunion; Soviet Union -- Foreign relations -- 1985-1991; Soviet Union -- Politics and government -- 1985-1991; Soviet Union -- Foreign relations -- Afghanistan; Afghanistan -- History -- Soviet occupation, 1979-1989; Afghanistan